Myocardial ischemia in neonate with perinatal asphyxia: Electrocardiographic, echocardiographic and enzymatic correlation - Merchant, Saira; Meshram, Rajkumar M; Khairnar, Devendra (Indian Journal of Child Health, 2016)
Objective: The objective of this study is to evaluate the presence and severity of cardiac involvement in asphyxiated neonates and to established which clinical and laboratory parameters (electrocardiogram [ECG], echocardiography [ECHO], and cardiac enzyme) are reliable predictors of myocardial ischemia. Design: Nested case–control study. Setting: Neonatology unit of tertiary care institute. Materials and Methods: The study group consist of 90 term neonates who had APGAR score <7 at 5 min as cases and 90 term neonate who had APGAR score >9 at 5 min as controls. On the 2nd day of life (between 24 and 36 h), all neonate underwent ECG, ECHO, and enzyme estimation (CK-MB). Result: The cases were divided into three groups according to SARNAT scale and Group I consist 25, Group II - 54, and Group - III, 11 neonates. The mean gestational age was 36.97±0.35 and 37.12±0.46 week for cases and controls respectively while mean birth weight was 2.79±0.36 kg and 2.68±0.76 kg for cases and controls, respectively. ECG changes were present in 70 (77.7%) of cases. ECG changes of Grade 3 and 4 were present in only Group III neonates and all neonates with Grade 4 changes were died in 1st week of life. Fractional shortening (FS) decreased progressively from Group I to Group III (p<0.001) and showed a significant difference between cases and controls as well as in different groups except in controls versus Group I. Peak aortic velocity behaved similarly. Concerning mean acceleration, the significant difference was observed between control and cases (all 3 groups). CK-MB activity increased from Group I to Group III and statistically significant difference was seen in controls and different Groups as well as in between different groups except in Controls versus Group I. Conclusion: Severe ECG changes (Grades 3 and 4), CK-MB elevation and reduced FS can be considered as reliable marker of myocardial ischemia in perinatal asphyxia.